Edukasi Fisioterapi Komunitas pada Pasien dengan Hipertensi di Posyandu Lansia RW. 3 Kelurahan Tulusrejo Puskesmas Kendalsari Kota Malang - Dheviana Ramadhani; Sri Sunaringsih Ika Wardojo; Bonita Suharto (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Hypertension is a condition of the blood circulation system that causes an increase in blood pressure above normal values ​​or blood pressure ≥140/90 mmHg. Prolonged increase in blood pressure can trigger the risk of stroke, heart failure, and kidney failure. Community service activities are one of the efforts to implement physiotherapy services, one form of counseling is by addressing problems that are widely complained about by the community. The purpose of the counseling is to provide knowledge about hypertension and how to do exercises to reduce neck pain independently at home. The method used is in the form of education and stretching exercises using leaflets as a counseling medium. Counseling is carried out by providing pre-tests and post-tests in the form of questions to patients to assess the effectiveness of the counseling that will be given to the elderly community. The results of the counseling went smoothly and from the evaluation there was an increase in participant knowledge from 0% to 100%, which in counseling activities can increase participant knowledge about how to deal with neck pain caused by hypertension.